ATRIAL FIBRILLATION - AMIT MATITYAHU; YARIV AVRAHAM AMOS; LIOR BOTZER; ELAD NAKAR; STANISLAV GOLDBERG; JONATHAN YARNITSKY; ELIYAHU RAVUNA (2021)
To provide a system and method for implementing a machine-learning/artificial-intelligence algorithm for detecting atrial fibrillation and atrial fibrillation termination.SOLUTION: A method is provided. The method is implemented by a detection engine embodied in a processor-executable code stored on a memory and executed by at least one processor. The method includes modeling a vector velocity field that measures and quantifies a velocity of electrocardiogram data signals that pass through a local activation time. The method further includes: determining codes for each point in a plane to provide a color-coded vector field image; detecting focal activation and rotor indications by using kernels to scan the color-coded vector field image; and classifying the focal activation and rotor indications into perpetuators.SELECTED DRAWING: Figure 1 【課題】心房細動及び心房細動終結を検出するための機械学習／人工知能アルゴリズムを実施するシステム及び方法を提供すること。【解決手段】方法が提供される。方法は、メモリ上に記憶され、少なくとも１つのプロセッサによって実行されるプロセッサ実行可能コードとして具体化される検出エンジンによって実施される。方法は、局所興奮時間を通過する心電図データ信号の速度を測定及び定量化するベクトル速度場をモデル化することを含む。方法は、平面内の各点についてコードを決定して、色コード化ベクトル場画像を与えることと、カーネルを使用して、色コード化ベクトル場画像をスキャンすることによって、巣状興奮及びローター指標を検出することと、巣状興奮及びローター指標を持続因子に分類することと、を更に含む。【選択図】図１